REVITALISASI POTENSI ANYAMAN BAMBU DESA LOYOK SEBAGAI SENTRAL PRODUK DESA WISATA - Tira, Hendry; Larasati, Mya Azmi; AJ, ADITYA; KHUZAIMA, NABILA DWI; ., Badrun; RAHMAN, FADLU; FILARDHI, MUHAMMAD KAUTSAR; Adiba, Nur; ASIAH, DWI; febriani, Putri kerlina; PUTRI, ALYA FADILLA; ANGGRAINI, BAIQ PUTRI BUNGA (Jurnal Bakti Nusa, 2025)
Real Work Lectures (KKN) is a student service program at the University of Mataram which aims to empower village communities. One of the KKN locations is Loyok Village, Sikur District, East Lombok Regency, which is known as a center for bamboo woven crafts. Since 1990, Loyok Village has exported woven bamboo products to various regions and abroad. However, after the 2002 Bali Bombing tragedy, the selling value of the product decreased, causing a decline in the interest of the younger generation in continuing this craft. Many craftsmen have changed professions due to low income. The main challenge is to restore the glory of Loyok Village as a tourist village based on woven bamboo. Through the KKN program, students strive to revitalize the village's potential with guidance, product innovation and marketing strategies to increase the competitiveness and desirability of the bamboo woven industry as a distinctive identity of Loyok Village.